Repetition as a realisation of the suggestive strategy of the English electoral discourse - Ilchenko, M.L. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article focuses on the analysis of repetition as a realisation of the strategy of suggesting the addressee of the English electoral discourse certain ideas through their recurrent instantiation by repeating lexemes, their structural and semantic derivatives, pronouns, word combinations and predications in parallel syntactic constructions within contact, anaphoric, epiphoric and framing patterns.
Keywords: English electoral discourse; suggestive strategy; repetition